The fear of COVID-19, health literacy and levels of compliance with prevention measures of adult individuals in Turkey - Yiğitalp, Gülhan (The Journal of Infection in Developing Countries, 2024)
Introduction: It is known that health literacy and fear of COVID-19 are effective in complying with COVID-19 prevention measures. A limited number of studies have shown the relationship between health literacy, fear of COVID-19, and compliance with COVID-19 prevention measures. The purpose of this study is to investigate the fear of COVID-19, health literacy, compliance levels with prevention measures of adult individuals and influential factors. Methodology: The cross-sectional study used an online questionnaire and was conducted with 1018 adults aged 18-64 in Turkey between 01-31 December 2020. The convenience sampling method was used to determine the sample. Student t-test, ANOVA, correlation, and multiple linear regression were used. Results: Half of the participants (49.9%) had inadequate and problematic-limited health literacy (HL). Adults` compliance with measures during the COVID-19 pandemic and some sociodemographic characteristics had a significant relationship with HL and fear of COVID-19 (p < 0.05). It was determined that those with high HL and those afraid of COVID-19 paid more attention to precautions (p < 0.05). Health literacy was a predictor of fear of COVID-19 (β = -0.091; p < 0.001). Conclusions: Governments need to invest in increasing health literacy.